“CAN’T BE SEEN AS AN OFFICIAL CLASS MEETING OR REPRESENTATIVE INSTITUTION”: REGULATIONS FOR THE CONGRESS OF ENTRUSTED KABARDIANS AND BALKARS IN ADMINISTRATIVE PROCEEDINGS - PRASOLOV, D.N. (Kavkazologiya, 2020)
On the basis of comparison of normative and materials the substantial features of activity regulations of congresses of trusted rural societies of Big and Small Kabardy and five mountain societies are studied. Normative functions of congresses of proxies in a limited form were approved only by a few fragments of decrees of Caucasian viceroys in 1860, 1905 and 1908. This order determined only the most general framework providing territorial representation of elected from villages at regular election of deputies and kady of district court, as well as the order of Zolski and Mountain public pastures under crown control of administration. More detailed regulation was revealed, which was carried out in administrative correspondence, which accompanied the preparation of the next congress. Circulars and orders initially determined the social composition of the trustees, agreed on the subpoena, the order of consideration and decision-making, the conditions of material and household support of the trustees in the district center, etc.  The conclusion was grounded that insufficient legislative certainty of functions of the congress of trustees was a convenient format for the crown authorities to organize judicial and administrative order in Nalchik district of Tersky oblast’. The lack of clear and detailed regulation left room for "administrative discretion" of situational management decisions, allowing more flexibility in directing public life of the local population.